Effect of Benzyl adenine and Naphthalene acetic acid in increasing dimeter and number of potato microtubers propagation in vitro - Hamza A. Ibraheem; Laith A. Hatem; Shatha A. yousif; Attallah I . Alwan; Abdulkareem R. Kadhim (Journal of Madenat Alelem University College, 2011)
The objective of this experiment was to study the effect of benzyl adenine BA and naphthalene acetic acid NAA at different concentrations 0,1, 2 and 3 mg / l as mellas to the effect of BA (0,1, 2 and 3 mg / L) and the presence of 2 mg / L NAA in the number and dimeter of the microtuber varieties of potato Desiree and Daimont cultivated in vitro. The results showed no significant differences between the two cultivars or interaction between the two cultivars and the concentrations of all treatments in the number and dimeter of the tubers. Although added each of BA and NAA increased significantly number of micro tubers compare with control treatment but there were no significant differences among the concentrations of each of BA and NAA, .While there were significant differences between the concentrations in the dimeter of the microtubers. The result showed that 2 mg NAA / liter gave maximum dimeter of microtuber (6.5 mm ) compared to different concentrations zero and 1 and 3 mg / L which the size of micro tubers were 0.75, 3.15 and 5.4 mm respectively. Added BA increased significantly the dimeter of microtubers compare with control treatment. The effect of different concentration of BA and the presence of NAA significantly increased the dimeter of the microtubers and the best treatment was 2 mg BA/l compare with others .